[Tuberculosis That Mimics Cancer: Cases Referred to the National Institute of Neoplastic Diseases, Lima-Peru] - Villena-Suarez, JR (2018)
Tuberculosis (TB) is a major public health problem that, due to the clinical variability of its presentation, can be confused with cancer. The aim of this study was to identify the clinical-radiological characteristics and to describe the methodology that allowed to achieve a TB diagnosis in patients referred to the National Institute of Neoplastic Diseases (INEN) with a presumed diagnosis of cancer between 2014 and 2016. The study included 170 patients (52.4% men) with an average age of 41.1 years; 18% presented a history of contact with TB, and 5.9% had had the disease previously. The TB was pulmonary in 22.4% and extrapulmonary in 77.7% of patients. The most frequent symptoms were respiratory, tumor, weight loss, and neurological. The cancer diagnoses most frequently discarded were lymphoma, lung cancer, and brain cancer. The lesions that suggested a neoplasm indicated an advanced clinical stage in 63.5%. Therefore, it follows that the symptoms and images associated with TB can be confused with malignant neoplasms.